Tanggung Jawab Sosial dan Tantangan Multikulturalisme di Era Modern - Sri Anisha Devi; Syabilah Sasmika Sari; Naya Nalamonda; Fitrah Fatahillah; Bisru Hafi (Yayasan Zia Salsabila, 2026)
ABSTRACT The modern era has created increasingly diverse societies through globalization, migration, technological advancement, and rapid cultural interaction. While diversity provides opportunities for innovation, cooperation, and cultural enrichment, it also creates challenges such as intolerance, stereotypes, discrimination, and social conflict. Therefore, social responsibility is essential in maintaining harmony within multicultural communities. This study aims to analyze forms of social responsibility and identify the challenges of multiculturalism in the modern era. The research employed a qualitative descriptive method using interviews, observation, and case study approaches. Five participants from different ethnic and professional backgrounds were selected as informants. The findings show that social responsibility is reflected through tolerance, mutual cooperation, empathy, respect for differences, and participation in social activities. However, significant challenges remain, including prejudice, hate speech on social media, economic inequality, and declining communal values in urban life. The study concludes that strengthening multicultural education, promoting digital literacy, and encouraging inclusive participation are necessary to create social cohesion and sustainable harmony in multicultural societies.